Using phenological niche separation to improve management in a Northern Glaciated Plains grassland. Issue 4 (11th March 2019) - Bennett, Joe; Smart, Alexander; Perkins, Lora
Abstract : Many of the remaining patches of untilled (native) prairie in the Northern Glaciated Plains of North America are heavily invaded by the cool‐season grasses, Bromus inermis and Poa pratensis . However, the native vegetation in these patches contains many warm‐season species. This difference in phenology can be used to benefit restoration. We conducted an experiment to examine the efficacy of restoration treatments (mowing and prescribed fire) applied early in the growing season for consecutive years to decrease cool‐season invasive plant biomass without impacting the native warm‐season species. Our treatments were successful at significantly decreasing invasive cool‐season plant biomass and increasing native warm‐season plant biomass. No differences between treatments (mowing and prescribed fire) were found. Results suggest that incorporating differences in phenology between target and nontarget species into management may increase restoration success.